2022
DOI: 10.3389/feduc.2022.933087
|View full text |Cite
|
Sign up to set email alerts
|

Visual images of the biological microcosmos: Viewers’ perception of realism, preference, and desire to explore

Abstract: Visual images are crucial for communicating science in educational contexts and amongst practitioners. Reading images contributes to meaning-making in society at large, and images are fundamental communicative tools in public spaces such as science centers. Here, visitors are exposed to a range of static, dynamic, and digital visual representations accessible through various multimodal and interactive possibilities. Images conveying scientific phenomena differ to what extent they represent real objects, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, two studies have revealed that higher levels of realism can result in better retention performance (or better performance for parts of a visualization that were rendered realistically), but at the same time increase subjective cognitive load (Skulmowski 2022a , b ; Skulmowski and Rey 2020 ). However, the desire to explore objects has been found to increase with higher levels of perceived realism (Höst et al 2022 ), providing another potential advantage of realistic visuals for learning. It should be considered that most positive effects of realism on learning pertain to the learning of shapes, while the learning of processes and abstract knowledge appears not to benefit from realistic details (Skulmowski et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two studies have revealed that higher levels of realism can result in better retention performance (or better performance for parts of a visualization that were rendered realistically), but at the same time increase subjective cognitive load (Skulmowski 2022a , b ; Skulmowski and Rey 2020 ). However, the desire to explore objects has been found to increase with higher levels of perceived realism (Höst et al 2022 ), providing another potential advantage of realistic visuals for learning. It should be considered that most positive effects of realism on learning pertain to the learning of shapes, while the learning of processes and abstract knowledge appears not to benefit from realistic details (Skulmowski et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%